The effect of local wake model on collision probability for risers subjected to current and random waves. (15th August 2018) - Fu, Ping; Leira, Bernt J.; Myrhaug, Dag
Abstract: The present paper provides a method to estimate the clearance between two flexible risers in tandem arrangement by taking into account the hydrodynamic wake interference when subjected to a current flow and a combined current plus waves flow. Modelling of the wake interference in the near wake field is based on the modification of the mean wake velocity deficit in the far wake field. Two modified wake models are introduced in the presented paper. The wake effects in steady current and in current plus waves are investigated by using both wake models. For the current-only flow, the deflection shapes of a pair of tandem risers in steep-wave configuration are presented, highlighting the importance of the wake effect on clearance estimation. For combined current plus waves, the wake interference is investigated by considering the position-dependent drag force, with different combinations of riser natural frequency and wave frequency. The collision failure probability is predicted when the risers are subjected to current plus random waves. Highlights: Two modified weak models are introduced and compared with the experimental results. The effect of the wake on the static deflection of a pair of risers is studied by using the software Riflex combined with the modified models. Wake interference in waves is investigated in current-dominated flow by updating the drag force at each time step. The collision probability is estimated from 25 one-hour simulations by using a Gumbel probability paper.